SURFACE FLOW REDUCTION AT APUDDLE AREA BY POROUS RECHARGE (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
Waterlogging occurs when rain is rain water that gathered accumulation exceeded the rainag capacity of the river and it is causedndue to the absence of absorption infiltration into the soil this the study aimed to assess the basic characteristics of the land area of inundation, (material volcanic rocks, and chunk) and infiltration capacity this research method is the study of soil mechanics laboratory experiments using soil samples from 2 nundation areas, areas not graceful and the samples of porous material and chunks of mountain rock (sand, cement, bricks) the result showed that the characteristics of waterlogged soil including silt soils kelempungan category and has a value of permeability 0.0002099 cm/sec, permeability volcanic rocks 0.04505 cm/s, permeability blocks (sand, cement, bricks) 0.02955 cm/sec. This suggests that the volcanic rocks have large permeability values that can be just passed substantial drainage. From the analysis carried out shows the reduction of surface water to echarge the mountain rock so big that can reduce surface runoff and can also recharge ground waterreserves.